Effect of a Polymeric Protective Coating on Optical and Electrical Properties of Poly(p-phenylene vinylene) Derivatives - Goncalves, V. C.; Olivati, C. A. [UNESP]; Carvalho, A. J. F.; Balogh, D. T. (Hindawi Publishing Corporation, 2013)
The resistance to photodegradation of poly[(2-methoxy-5-n-hexyloxy)-p-phenylene vinylene] (OC1OC6-PPV) films was significantly enhanced by the use of poly(vinyl alcohol) 99% hydrolyzed as protective coating. The deposition of poly(vinyl alcohol) onto OC1OC6-PPV films did not affect the absorption and the emission spectra of the luminescent polymer. The protected film showed 5% drop on the absorbance at 500 nm after 270 hours of light exposure while the unprotected film completely degraded in the same conditions. The conductivity of the protected film remained stable (around 7 x 10(-10) S/m) while the value for the unprotected one dropped around two orders of magnitude after 100 hours of light exposure.